Microstrip Passive Components for Energy Harvesting and 5G Applications: A Comprehensive Review - Nouri, Leila; Yahya, Salah I.; Rezaei, Abbas; Majidifar, Sohrab (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
This review paper provides a comprehensive overview of microstrip passive components for energy harvesting and 5G applications. The paper covers the structure, fabrication and performance of various microstrip passive components such as filters, couplers, diplexers and triplexers. The size and performance of several 5G and energy harvester microstrip passive devices are compared and discussed. The review highlights the importance of these components in enabling efficient energy harvesting and high-speed communication in 5G networks. Additionally, the paper discusses the latest advancements in microstrip technology and identifies key research challenges and future directions in this field. Overall, this review serves as a valuable resource for researchers and engineers working on microstrip passive components for energy harvesting and 5G applications.